Examining the paradoxical effects of kratom: a narrative inquiry - Smith, Kirsten E.; Feldman, Jeffrey D.; Dunn, Kelly E.; McCurdy, Christopher R.; Weiss, Stephanie T.; Grundmann, Oliver; Garcia-Romeu, Albert; Nichels, Janeen; Epstein, David H. (Frontiers in Pharmacology, 2023)
Several surveys and case reports have documented kratom use in the United States (US) for over a decade. However, little is known about kratom effects or the role kratom plays in the lives of those who use kratom products regularly for sustained periods. In the absence of much-needed controlled clinical studies investigating the pharmacology and subjective effects of kratom alkaloids, the best method for currently understanding US kratom product use remains self-report. However, there are few qualitative data that provide nuanced descriptions of kratom effects among those who use it regularly. These are needed to inform the broader drug policy and public health context of kratom but may also help inform future experimental designs. Here, we conducted semi-structured qualitative interviews with regular kratom-using adults as part of a laboratory study of kratom product self-administration. This qualitative component of the study was conducted to characterize participants’ kratom use history as a narrative case-report series (n=10). We found that despite participant differences, all experienced acute combination effects that were largely, even simultaneously, analgesic, and stimulatory. Participants mostly decreased kratom dosing over time, and one planned to quit. DSM-5 substance use disorder assessed for kratom, indicated the following severity across 5/10 participants: 3 mild, 1 moderate, 1 severe. A constellation of symptoms independently described by participants when excess kratom was inadvertently taken indicates possible serotonergic excess. Occurrence was rare but requires follow-up. Most participants described tolerance but considered kratom at low-moderate doses generally safe, natural, and beneficial with less potential risk for adverse effects compared to pharmaceuticals or illicit drugs.